2005
DOI: 10.1111/j.1532-5415.2005.53556.x
|View full text |Cite
|
Sign up to set email alerts
|

Experts Recommend Strategies for Strengthening the Use of Advanced Practice Nurses in Nursing Homes

Abstract: In 2003, The John A. Hartford Foundation Institute for Geriatric Nursing, New York University Division of Nursing, convened an expert panel to explore the potential for developing recommendations for the caseloads of advanced practice nurses (APNs) in nursing homes and to provide substantive and detailed strategies to strengthen the use of APNs in nursing homes. The panel, consisting of nationally recognized experts in geriatric practice, education, research, public policy, and long‐term care, developed six re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 17 publications
(45 reference statements)
0
30
0
Order By: Relevance
“…A prior study recommended changes in Medicare physician and APN reimbursement to reflect the value of currently nonbillable practitioner time (Mezey et al, 2005). Building on those previous recommendations, the expert panel recommended adjusting RVUs to reflect the increasingly complex needs of short-and long-term care nursing home residents.…”
Section: Rvu Codingmentioning
confidence: 96%
See 1 more Smart Citation
“…A prior study recommended changes in Medicare physician and APN reimbursement to reflect the value of currently nonbillable practitioner time (Mezey et al, 2005). Building on those previous recommendations, the expert panel recommended adjusting RVUs to reflect the increasingly complex needs of short-and long-term care nursing home residents.…”
Section: Rvu Codingmentioning
confidence: 96%
“…Drawing on empiric evidence and clinical expertise, the panel developed six recommendations related to APN use: (a) increase the presence of APNs in nursing homes; (b) add geriatric content to APN educational preparation; (c) delineate resident, facility, and practitioner factors that influence the number and type of APN visits per day; (d) restructure APN reimbursement to account for nonbillable activities related to resident care; and (e) describe the technical assistance necessary to facilitate APN practice in nursing homes. Details of these six panel recommendations have been published elsewhere (Mezey et al, 2005).…”
mentioning
confidence: 99%
“…7,8,14,24,25 The need for further education and better preparation of healthcare providers to manage these symptoms is quite clear. 19 There can be little doubt that without standardized, formal education, NPs are unlikely to have the necessary knowledge base upon which to properly manage symptoms at and near the end of life. Indeed, a gap very likely exists between the best palliative care practices and the usual practices as provided by NPs in nursing homes.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Studies have demonstrated the effectiveness of NPs in providing cost-effective, quality care in nursing homes. 16 Given their education and training in patient assessment, coordination of care, and communication skills, NPs are well suited to direct and deliver care to patients who are living with, and dying of, progressive disease.…”
Section: Introductionmentioning
confidence: 99%
“…For example, higher levels of educational preparation and specialty knowledge in nursing homes have been related to more effective RN leadership and supervisory skills (Fleming & Kayser-Jones, 2008; Siegel, Young, Mitchell, & Shannon, 2008). Nursing home use of advanced practice nurses (APNs) has been related to better resident quality of care outcomes (Kane, Keckhafer, Flood, Bershadsky, & Siadaty, 2003; Lekan, Hendrix, McConnell, & White, 2010; Mezey et al, 2005). A higher proportion of RNs among nursing home staff, as well as having overall higher RN staffing levels, have been linked to better quality of care (Akinci & Krolikowski, 2005; Anderson, Hsieh, & Su, 1998; Bostick, 2004; Castle, 2002; Horn et al, 2005; Weech-Maldonado, Meret-Hanke, Neff, & Mor, 2004).…”
mentioning
confidence: 99%